Bobot badan dan ukuran linier tubuh umur empat minggu ayam hasil silangan antara beberapa strain ayam jantan dengan betina lokal sabu - Haryanto Ndruru; Franky M. S Telupere; Djegho Yohanes (Jurnal Peternakan Lahan Kering, 2019)
The study aimed to examine the body size of crossbred from several strains of cocks with local Sabu hens. The research method was used Completely Randomized Design with three treatments and four replications. The material used was 15 head of chickens (3 males and 12 females) and 48 progenies. The variables measured were body weight, chest circumference, wingspan and shank length at four weeks of age. Data were analyzed using analysis of variance and if there were found significantly effect, it woull be continued with the least significant difference test (LSD). The results showed that the treatment (males) had a highly significant effect (P<0.01) on body weight and wingspan, significant effect (P<0.05) to the chest circumference and not significant effect (P>0.05) on shank length of the crosbred of local Sabu hens. Based on the results obtained, it could be concluded that the crossbreeding between the laying cock with the hens oflocal Sabu hadprogenies with the best body size performances.